BOOK REVIEWS (Heythrop journal, 1991)
The Book of Ruth (The New International Commentary on the Old Testament). By Robert L. Hubbard. A Reordering of Power: A Socio-Political Reading of Mark's Gospel. By Herman C. Waetjen. Paul and Jesus: Collected Essays (JSNT Supplement Series 37). Edited by A.J.M. Wedderburn. The Study of Literature and Religion (Studies in Literature and Religion). By David Jasper. Faith and the Play of Imagination: On the Role of Imagination in Religion (Studies in American Biblical Hermeneutics 5). By David J. Bryant. Homer or Moses? Early Christian Interpretations of the History of Culture (Hermeneutische Untersuchungen zur Theologie 26). By Arthur J. Droge. Denys the Areopagite (Outstanding Christian Thinkers). By Andrew Louth. Decrees of the Ecumenical Councils. Edited by Norman P. Tanner. Divine Nature and Human Language: Essays in Philosophical Theology. By William P. Alston. Theological Essays. By Eberhard Jüngel, edited by J.B. Webster. Faithful Witness: Foundations of Theology for Today's Church. Edited by Leo J. O'Donovan and T. Howland Sanks. From Unity to Pluralism: The Internal Evolution of Thomism. By Gerald A. McCool. Religion and Twentieth-Century American Intellectual Life. Edited by Michael J. Lacey. Thinking the Faith: Christian Theology in a North American Context. By Douglas John Hall. African Catholicism: Essays in Discovery. By Adrian Hastings. Emancipation in African Theology: An Inquiry on the Relevance of Latin American Liberation Theology to Africa (American University Studies VII/14). By Victor Wan-Tatah. Anglo-Catholicism: A Study in Religious Ambiguity. By W.S.F. Pickering. The Church and Secularisation: Urban Industrial Mission in North East England. By Michael S. Northcott. Religion and Advanced Industrial Society (Controversies in Sociology 23). By James A. Beckford. Religion, Interpretation and Diversity of Belief: The Framework Model from Kant to Durkheim to Davidson. By Terry F. Godlove. Religion, Science and Magic — In Concert and In Conflict. Edited by J. Neusner, E. Frerichs and P.V. McCracken Flesher. A Dictionary of Superstitions. Edited by Iona Opie and Moira Tatem. The Churches, Ireland and the Irish (Studies in Church History 25). Edited by W.J. Shells and Diana Wood. John of Wales: A Study of the Works and Ideas of a Thirteenth-Century Friar (Cambridge Studies in Medieval Life and Thought 10). By Jenny Swanson. Church and Society in Late Medieval England. By R.N. Swanson. Ecclesia Anglicana: Studies of the English Church in the Later Middle Ages. By Roy Martin Haines. ‘Piers Plowman’and the New Anti-Clericalism (Cambridge Studies in Medieval Literature). By Wendy Scase. Thomas Müntzer: Theology and Revolution in the German Reformation. By Tom Scott. Jesuit Geometers. By Joseph MacDonnell. The Europe of the Devout: The Catholic Reformation and the Formation of a New Society (Past and Present Publications). By Louis Châtellier, translated by Jean Birrell. You Looked at Me: The Spiritual Testament of Claudine Moine. Translated will commentary by Gerald Carroll. Reviving Liberty: Radical Christian Humanism in Milton's Great Poems. By Joan S. Bennett. Pascal's Lettres Provinciales: A Study in Polemic. By Richard Parish. A Social History of French Catholicism 1789–1914. By Ralph Gibson. Al-Muwatta of Imam Malik ibn Anas: The First Formulation of Islamic Law. The Islamic Classical Library. Translated by Aisha Abdurrahman Bewley. Montesquieu: the Spirit of the Laws (Cambridge Texts in the History of Political Thought). Translated and edited by Anne M. Cohler, Basia Carolyn Miller and Harold Samuel Stone. Spinoza and Other Heretics. By Yirmiyahu Georg Wilhelm Friedrich Hegel: Lectures on the Philosophy of Religion, One Volume Edition The Lectures of 1827. Edited by Peter C. Hodgson. Heidegger's Estrangements: Language, Truth and Poetry in the Later Writings. By Gerald L. Bruns. What is a Person? The Concept and Implications for Ethics (Problems in Contemporary Philosophy 21). By Kevin Doran. Christian Neighbor-Love: An Assessment of Six Rival Versions. By Garth L. Hallett. Moral Realism and the Foundation of Ethics (Cambridge Studies in Philosophy). By David O. Brink. Ethics in the Natural Sciences (Concilium 203). Edited by Dietmar Meith and Jacques Pohier.